Comparison of the Nature of Science Between Thematic and Non-Thematic Science Textbooks in Elementary School - Fhilrizki, Salma Ihsani; Nurdinilah, Siti Alfi; Sritiawati, Tia; Widodo, Ari (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2022)
This study aims to analyze the differences in the nature of science in thematic textbooks and non-thematic science textbooks in elementary schools. The study approach used is qualitative with a descriptive method. The subjects in this study were thematic textbooks and three non-thematic science textbooks in grade VI elementary school. The data collection technique used is a documentation study by analyzing the concept of the nature of science in each of the essential competencies presented in the book, the results of the analysis in the Textbook are analyzed descriptively and presented in percentage form. This study indicates a difference between aspects of the nature of science in thematic and non-thematic science textbooks in grade VI elementary school. Non-Thematic textbooks have a higher percentage of science's nature than the nature of science in thematic textbooks. The product aspect has the highest rate, 97%, and the lowest aspect is the creativity aspect, which is 25%. This study is fundamental to analyze in detail the components of science's nature, which can later be used as a basis by teachers in choosing science textbooks in elementary schools so that learning can be carried out correctly and the nature of science can be taught to students.